KENDALA GURU MEMOTIVASI SISWA DALAM PROSES PEMBELAJARAN DI SD NEGERI 46 BANDA ACEH - Indah Purnama; Nurhaidah M. Insya Musa; Mislinawati Mislinawati. (Jurnal Pesona Dasar, 2018)
This study entitled teacher constraints motivate students in the learning process in public elementary school 46 Banda Aceh. As for the formulation of the problem in this research is (1) what are the efforts made in motivating students to learn at elementary school 46 Banda Aceh and (2) what are the contraints of teacher in motivating students on the learning process at elementary school 46 Banda Aceh. This study aims to describe the efforts of teacher to motivate students in the learning process and teacher constraints to motivate students in the learning process at elementary school 46 Banda Aceh. This research uses qualitative approach an deskriptive research type. The subjects in this study class teachers amounted to 6 people. Data collection is done by using observation sheets and interviews of teacher activities in the learning process in the classroom. While the data processing using guttman scale, using three stages of qualitative data analysis, namely; data reduction, display data, and drawing conclutions. Based on the results of observations and interviews can be concluded the existence of the teachers efforts in motivating students like, make good communication between students and parents, give verbal and non verbal reinforcement clearly, establish deep emotional relationships with students. Obstacles experienced by teachers among others, First, the verbalistic constraint of lack of understanding from students. Second, the interindividual constraint is that not all students are active. Third,  the environmental barrier is the lack of cooperation between parents and teacher. It is recommended that teachers build good relationships with students and parents.